NEWS AGENCIES AS PROPAGANDA SUBJECTS IN THE MODERN WAR AGAINST UKRAINE (Coordinates of Public Administration, 2026)
The article examines the role of news agencies as important propaganda subjects in the modern war against Ukraine, where the information space is one of the key areas of hybrid confrontation. It is substantiated that in the conditions of the Russian-Ukrainian war, news agencies cease to be only intermediaries in the transmission of news and increasingly function as instruments of targeted political influence, legitimization of aggression, formation of a distorted picture of reality and manipulation of mass consciousness. The author emphasizes that the specificity of the activities of such agencies lies in the combination of efficiency, apparent objectivity and wide audience coverage, which gives propaganda messages signs of credibility and strengthens their influence both within the aggressor state and beyond its borders. It is proven that Russian news agencies in modern warfare perform the functions of constructing and replicating strategic narratives aimed at delegitimizing Ukrainian statehood, justifying military aggression, discrediting the Armed Forces of Ukraine, demoralizing society, and disorienting the international community. Considerable attention is paid to the mechanisms of disguising propaganda as neutral news content, as well as the analysis of lexical, semantic, and communicative technologies by which news agencies transform facts into politically advantageous interpretations. It is emphasized that in the conditions of information warfare, not only the content of messages but also the institutional nature of the media, the degree of their dependence on state power, and their inclusion in the aggressor’s strategic communications system are of particular importance. As a result, the conclusion is made that information agencies in the modern war against Ukraine should be considered as a component of the infrastructure of hybrid aggression, and their research is important for understanding the mechanisms of propaganda, strengthening information security and developing effective means of countering disinformation influence.